Answer:
[tex]cos^2\theta + sin^2\theta = 1[/tex]
Step-by-step explanation:
Given
[tex](\frac{b}{r})^2 + (\frac{a}{r})^2[/tex]
Required
Use the expression to prove a trigonometry identity
The given expression is not complete until it is written as:
[tex](\frac{b}{r})^2 + (\frac{a}{r})^2 = (\frac{r}{r})^2[/tex]
Going by the Pythagoras theorem, we can assume the following.
So, we have:
[tex]Sin\theta = \frac{a}{r}[/tex]
[tex]Cos\theta = \frac{b}{r}[/tex]
Having said that:
The expression can be further simplified as:
[tex](\frac{b}{r})^2 + (\frac{a}{r})^2 = 1[/tex]
Substitute values for sin and cos
[tex](\frac{b}{r})^2 + (\frac{a}{r})^2 = 1[/tex] becomes
[tex]cos^2\theta + sin^2\theta = 1[/tex]